VD_FINDINFO Décision / 2011 / 680 vom 31. August 2011 - VD Tribunal cantonal (2011)
NON-LIEU, DÉCISION D'IRRECEVABILITÉ, CONTRAINTEDROIT PÉNAL, MENACEDROIT PÉNAL | 310 CPP (CH), 393 al. 1 let. a CPP (CH)